2020
DOI: 10.3389/fonc.2020.00397
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment: Extracellular Matrix Alterations Influence Tumor Progression

Abstract: The tumor microenvironment (TME) is composed of various cell types embedded in an altered extracellular matrix (ECM). ECM not only serves as a support for tumor cell but also regulates cell-cell or cell-matrix cross-talks. Alterations in ECM may be induced by hypoxia and acidosis, by oxygen free radicals generated by infiltrating inflammatory cells or by tumor-or stromal cell-secreted proteases. A poorer diagnosis for patients is often associated with ECM alterations. Tumor ECM proteome, also named cancer matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
144
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 163 publications
0
144
0
1
Order By: Relevance
“…The NC1 domains of the different α(IV) collagen chains were reported to exert anti-tumor or anti-angiogenic effects (Mundel and Kalluri, 2007;Monboisse et al, 2014;Brassart-Pasco et al, 2020). We and others demonstrated that the anti-tumor activities of Tumstatin or Tetrastatin were mediated through binding to α v β 3 integrin at the tumor cell surface (Pasco et al, 2000;Brassart-Pasco et al, 2012;Lambert et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…The NC1 domains of the different α(IV) collagen chains were reported to exert anti-tumor or anti-angiogenic effects (Mundel and Kalluri, 2007;Monboisse et al, 2014;Brassart-Pasco et al, 2020). We and others demonstrated that the anti-tumor activities of Tumstatin or Tetrastatin were mediated through binding to α v β 3 integrin at the tumor cell surface (Pasco et al, 2000;Brassart-Pasco et al, 2012;Lambert et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Collagens play structural roles in the mechanical properties of tissues and can interact with cells via several receptor families to regulate cell proliferation, migration, and differentiation [49] . Enrichment analysis revealed that these genes in Module 1 were enriched in many cancer-related pathways, including focal adhesion [50] , the PI3K-Akt signaling pathway [47] , collagen degradation [51] , and pathways in cancer. We also found that MeDEGs in Module 2 were related to the immune system, chemokine signaling pathway, and signaling by interleukins.…”
Section: Discussionmentioning
confidence: 99%
“…The GSEA revealed that the terms cytokine-cytokine receptor interaction, ECM-related, adhesion receptor interaction, cell adhesion molecules cams, focal adhesion, and immune cell related pathways were signi cantly enriched in IGFBP7 high expression phenotype. It has been reported that ECM components such as collagen, broblasts and their associated signaling molecules contribute to tumor cell proliferation, migration and invasion in various cancers [40,41]. Moreover, IGFBP7 has been reported to regulate epithelial-mesenchylmal transition (EMT) in some solid tumors [12,42,43].…”
Section: Discussionmentioning
confidence: 99%